Latitude, Elevation, and Mean Annual Temperature Predict Peat Organic Matter Chemistry at a Global Scale. Issue 2 (13th February 2022) - Verbeke, Brittany A.; Lamit, Louis J.; Lilleskov, Erik A.; Hodgkins, Suzanne B.; Basiliko, Nathan; Kane, Evan S.; Andersen, Roxane; Artz, Rebekka R. E.; Benavides, Juan C.; Benscoter, Brian W.; Borken, Werner; Bragazza, Luca; et al.
Abstract: Peatlands contain a significant fraction of global soil carbon, but how these reservoirs will respond to the changing climate is still relatively unknown. A global picture of the variations in peat organic matter chemistry will aid our ability to gauge peatland soil response to climate. The goal of this research is to test the hypotheses that (a) peat carbohydrate content, an indicator of soil organic matter reactivity, will increase with latitude and decrease with mean annual temperatures, (b) while peat aromatic content, an indicator of recalcitrance, will vary inversely, and (c) elevation will have a similar effect to latitude. We used Fourier Transform Infrared Spectroscopy to examine variations in the organic matter functional groups of 1034 peat samples collected from 10 to 20, 30–40, and 60–70 cm depths at 165 individual sites across a latitudinal gradient of 79°N–65°S and from elevations of 0–4, 773 m. Carbohydrate contents of high latitude peat were significantly greater than peat originating near the equator, while aromatic content showed the opposite trend. For peat from similar latitudes but different elevations, the carbohydrate content was greater and aromatic content was lower at higher elevations. Higher carbohydrate content at higher latitudes indicates a greater potential for mineralization, whereas the chemical composition of low latitude peat is consistent with their apparent relative stability in the face of warmer temperatures. The combination of low carbohydrates and high aromatics at warmer locations near the equator suggests the mineralization of high latitude peat until reaching recalcitrance under a new temperature regime. Plain Language Summary: Peatlands are a large global soil carbon reservoir, containing a quantity of carbon that is equivalent to about half or more of the carbon dioxide in the atmosphere. What will be their fate on a warming planet? Across a latitudinal gradient from 79°N to 65°S, we measured the fraction of the peat made up of carbohydrates, which are easily decomposed, and of aromatics, which are less easily decomposed. We found that peat from high latitudes and high elevations had greater carbohydrate content, while aromatic content showed the opposite trend. Larger carbohydrate content in organic matter indicates greater decomposability, while greater aromatic content indicates lower decomposability. We suggest that this latitude/elevation difference that we observed predicts how high‐latitude and high‐elevation peats may change under warmer conditions. Our work indicates that while a large portion of the carbohydrate fraction in these peats could be lost upon warming, releasing greenhouse gases, a residual fraction will survive and become more aromatic‐rich, making the remainder more resistant to rapid decomposition. Key Points: Peatland soil organic matter stability can be evaluated through the relative abundances of carbohydrate and aromatic content in peat Peat at higher latitudes and elevations has larger carbohydrate and smaller aromatic content relative lower latitudes and elevations Our results foreshadow a transition of organic matter from higher latitude peatlands to a more recalcitrant form in response to warming